(untitled) (Bangladesh Journal of Medicine, 2016)
Pattern of mortality gives a picture of disease burden of a community and helps in evaluation of health care system. A retrospective study was done in medicine wards of a tertiary care hospital in Bangladesh from 1st July 2014 to 30st June 2015 to see the mortality pattern. Data obtained from death and admission registrar. Total 1306 deaths were recorded. Mortality rate was 7%. Male female ratio was 1.65:1. Average age at death was 56.05 years. Highest 11.3% death occurred in January, 48.6% deaths occurred during night shift. Average stay in hospital was 42.1 hours. Non communicable disease causing 87%, communicable disease causing 8.8% deaths and 4.2% were brought dead and undiagnosed. Stroke and IHD caused 54.1% deaths. Among diagnosed causes, ratio of NCD and CD was 9.9:1. Bangladesh J Medicine Jan 2016; 27(1) : 22-26